The infrastructures of security: technologies of risk management in Johannesburg - Murray, Martin Julius (African perspectives, 2022)
"In The Infrastructures of Security, author Martin J. Murray concentrates on not only the turn toward technological solutions to managing the risk of crime through digital (and software-based) surveillance and automated information systems, but also the introduction of somewhat bizarre and fly-by-night experimental "answers" to perceived risk and danger. Digitalized surveillance is significant for two reasons: first, it enables monitoring to take place across wide "geographical distances with little time delay"; and second, it allows for the active sorting, identification, and "tracking of bodies, behaviors, and characteristics of subject populations on a continuous, real-time basis." These new software-based surveillance technologies represent monitoring, tracking, and information gathering without walls, towers, or guards"--